Sequential rearrangement and nuclear polymerization of actin in baculovirus-infected Spodoptera frugiperda cells. - Charlton, C A (1991)
Proper assembly of nucleocapsids of the baculovirus Autographa californica nuclear polyhedrosis virus is prevented by cytochalasin D, a drug that interferes with actin microfilament function. To investigate the involvement of microfilaments in A. californica nuclear polyhedrosis virus replication, a fluorescence microscopy study was conducted that correlated changes in distribution of microfilaments with events in the life cycle of the virus. Tetramethylrhodamine isothiocyanate-labeled phalloidin was used to label microfilaments, and monoclonal antibody was used to label p39, the major viral capsid protein. Three microfilament arrangements were found in infected cells. During uptake of virus, thick cables were formed. These were insensitive to cycloheximide, indicating that this configuration was a rearrangement of preexisting cellular actin mediated by a component of the viral inoculum. At the time of cell rounding and before viral DNA replication, ventral aggregates of actin were observed. These were sensitive to cycloheximide but not to aphidicolin, indicating that an early viral gene mediated this actin rearrangement. Ventral aggregates did not result from the rounding process itself. Uninfected cells prerounded with colchicine did not form ventral aggregates. Cells prerounded with colchicine and then infected did form aggregates. At the time of exponential production of progency virus, microfilaments were found in the nucleus surrounding the virogenic stroma. In this area (where nucleocapsid assembly is known to take place) microfilaments colocalized with p39. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis and Western immunoblot analysis identified p39 among proteins retained on an f-actin affinity column. We postulate that microfilaments in the nucleus provide a scaffold to position capsids for proper assembly and filling with DNA.